2010
DOI: 10.1073/pnas.0913149107
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative behavior cascades in human social networks

Abstract: Theoretical models suggest that social networks influence the evolution of cooperation, but to date there have been few experimental studies. Observational data suggest that a wide variety of behaviors may spread in human social networks, but subjects in such studies can choose to befriend people with similar behaviors, posing difficulty for causal inference. Here, we exploit a seminal set of laboratory experiments that originally showed that voluntary costly punishment can help sustain cooperation. In these e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
497
4
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 639 publications
(532 citation statements)
references
References 50 publications
17
497
4
3
Order By: Relevance
“…Combining contributions over many rounds therefore artificially amplifies the differences, leading to the appearance of statistical significance where none may exist. In fact, as Table 5 in [27] itself makes clear, the final (and also average) difference between topologies is roughly the same as the initial difference (period [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; thus essentially all of the difference can be explained in term of initial contributions, which are by construction unrelated to the network topology. Second, the significance of the NetworkClustering and NetworkLength coefficients in the PD1 logit model (Table 10 in [27]) is marginal and disappeared when other factors, such as the % cooperation in the previous experiment (PD2) or dummy variables for the session (PD3) were included.…”
Section: Testing For Effects Of Network Structurementioning
confidence: 79%
See 2 more Smart Citations
“…Combining contributions over many rounds therefore artificially amplifies the differences, leading to the appearance of statistical significance where none may exist. In fact, as Table 5 in [27] itself makes clear, the final (and also average) difference between topologies is roughly the same as the initial difference (period [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; thus essentially all of the difference can be explained in term of initial contributions, which are by construction unrelated to the network topology. Second, the significance of the NetworkClustering and NetworkLength coefficients in the PD1 logit model (Table 10 in [27]) is marginal and disappeared when other factors, such as the % cooperation in the previous experiment (PD2) or dummy variables for the session (PD3) were included.…”
Section: Testing For Effects Of Network Structurementioning
confidence: 79%
“…Specifically, Fowler and Christakis reanalyzed data from Fehr and Gachter [32] (the same results that we replicated in our preliminary experiments described above) in which groups of n~4 players were randomly reassigned to new groups after each round. Whereas in our networks, all individuals appear just once and play with same set of neighbors each turn, in [20] each individual appears r times (where r is the number of rounds of the experiment) and plays with a different set of neighbors each time. As a result, the measure of network distance in [20] does not map precisely to the conventional meaning of network distance, which is the meaning that we have adopted here, but rather refers at least in part to the relation between an individual's present and past states.…”
Section: Comparison Of Results With Fowler and Christakismentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have examined the social contagion effects of prosociality in experimental economic games, and found that generous allocations of resources could indeed spread from person to person (DeSteno, Bartlett, Baumann, Williams, & Dickens, 2010;Fowler & Christakis, 2010;Gray, Ward, & Norton, 2014). In an economic exchange game, for example, participants who had been helped by another gave more money to a stranger than those who had not been helped-a pay-it-forward effect (DeSteno et al, 2010).…”
Section: Who Spreads Prosociality?mentioning
confidence: 99%
“…In an economic exchange game, for example, participants who had been helped by another gave more money to a stranger than those who had not been helped-a pay-it-forward effect (DeSteno et al, 2010). In a multi-round economic game in which participants were constantly changing partners, giving more money to a partner instead of keeping it increased the partner's voluntary donations to others in subsequent rounds (Fowler & Christakis, 2010). Experimental studies that include both givers and receivers can be difficult to design without the use of economic games.…”
Section: Who Spreads Prosociality?mentioning
confidence: 99%